2017
DOI: 10.1186/s12944-016-0388-z
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-oxidized high density lipoprotein impairs atherosclerotic plaque stability by inhibiting smooth muscle cell migration

Abstract: BackgroundHigh density lipoprotein (HDL) has been proved to be a protective factor for coronary heart disease. Notably, HDL in atherosclerotic plaques can be nitrated (NO2-oxHDL) and chlorinated (Cl-oxHDL) by myeloperoxidase (MPO), likely compromising its cardiovascular protective effects.MethodHere we determined the effects of NO2-oxHDL and Cl-oxHDL on SMC migration using wound healing and transwell assays, proliferation using MTT and BrdU assays, and apoptosis using Annexin-V assay in vitro, as well as on at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…The latter observation is in line with the ability of chlorinated and nitrated HDL to inhibit SMC migration and exhibit a reduced ability to stimulate SMC proliferation, without significant effects on SMC apoptosis [153]. Furthermore, in experimental models of carotid stenosis, the injection of chlorinated or nitrated HDL resulted in increased neointima/media ratio and reduced SMC positive staining cells in the fibrous cap compared to native HDL-treated mice, thus suggesting that MPO-HDL might increase the vulnerability index of the plaque [153].…”
Section: Myeloperoxidase-induced Modification Of Hdlsupporting
confidence: 77%
“…The latter observation is in line with the ability of chlorinated and nitrated HDL to inhibit SMC migration and exhibit a reduced ability to stimulate SMC proliferation, without significant effects on SMC apoptosis [153]. Furthermore, in experimental models of carotid stenosis, the injection of chlorinated or nitrated HDL resulted in increased neointima/media ratio and reduced SMC positive staining cells in the fibrous cap compared to native HDL-treated mice, thus suggesting that MPO-HDL might increase the vulnerability index of the plaque [153].…”
Section: Myeloperoxidase-induced Modification Of Hdlsupporting
confidence: 77%
“…In this case, in contrast to observations with native apoA1, apoA1 oxidized by MPO failed to decrease macrophage number in the lesions or promote a noninflammatory macrophage phenotype (101). Finally, HOCl-induced modification of HDL inhibits the migration and proliferation of VSMC (311). This suggests that MPO-dependent HDL modifications can potentially promote inflammation, lesion development, and plaque instability in atherosclerosis.…”
Section: Lipoproteinscontrasting
confidence: 56%
“…Khine HW et al [ 5 ] showed that increased MPO indexed to HDL particle concentration (MPO/HDLp) is associated with increased risk of incident CVD (cardiovascular disease) events in a population initially free of CVD. MPO may contribute to atherosclerotic plaque instability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%